Relationship between Self Care and Quality of Life for Pregnant Women with Diabetes Mellitus Patients - Hastuti Hastuti; Afrina Januarista; Nelky Suriawanto (Science Midwifery, 2018)
Diabetic mellitus is the disease signed by increasing of blood sugar levels and could be immediately be cured instantly but need self care. Self care is individual planning action in controlling the disease to improve the health and life quality. The aims of this research to analyze the correlation between self care and life quality of diabetes mellitus patients in Garuda Ward of Anutapura General Hospital Palu. This is quantitative research it used analysis design with cross sectional approaching. Data is taken by using questions of summary of self care (SDSCA) and diabetes quality of life (DQOL) and samples taken by total sampling technique. The population number was 30 respondents and used univariate and bivariate analyzes with chi-square tests. Result found that more respondents have good self care (70%) with good quality of life (73. 3%) and chi-square test result that p value = 0.003 (p value <0.05) it means statistically having corellation between self care and quality of life. Conclusion that having a correlation between self care with quality of life diabetes mellitus patient in Garuda Ward of Anutapura General Hospital Palu. Patient diabetes mellitus expeeted cold improve the self care at the age of incerasing quality of life, health state and prevent the further complication.